Influence of outsourcing on innovativeness and characteristics of hotel enterprises in the Dubrovnik-Neretva county - Želimir Dulčić; Zdenko Klepić; Goran Vučur (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose - The paper aims to explore the application of outsourcing in hotel enterprises in the ubrovnik-Neretva County. The purpose of the paper is to explore the correlation between outsourcing and innovativeness of hotel companies. Design/methodology/approach - The hypothesis is that an increase in the level of outsourcing is related to a higher degree of innovation of hotel enterprises. We will analyze innovations in the tourism sector related to the introduction of new products and services, technological equipment and software, new activities and organization of business operations, as well as innovations in the field of marketing. Findings - Quick response to market changes and raising the level of ompetitiveness are considered to be key factors of business of hotel enterprises. Strategic management of hotel enterprises involves the use of different tools that help improve the business performance. Outsourcing of activities can be used as an option that facilitates the improvement of business operations. By using outsourcing, an enterprise tries to improve a variety of business segments that are included in the internal organization of the business, thereby trying to meet the needs of consumers. An important factor in business of an enterprise is innovation that results in creating comparative advantage over competitors. Research limitations/implications - The research was limited to a period of one year and includes area of Dubrovnik-Neretva Countyin Republic of Croatia. Originality/value - The research will be focused on the application of outsourcing in hotel enterprises, where it is planned to investigate the activities that are separated the most and their importance for the company's business. Attention will also be focused on characteristics of hotel enterprises with regard to outsourcing.
Keywords: L20; 330; outsourcing; innovativeness; characteristics of hotel enterprises